2013
DOI: 10.1074/jbc.m112.419358
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Stability of Replicative DNA Helicases upon Encountering DNA-Protein Cross-links

Abstract: Background: DNA-protein cross-links (DPCs) are formed by DNA-damaging agents. Results: DPCs on the translocating strand but not on the nontranslocating strand block hexameric replicative helicases in a size-dependent manner. Stalled helicases dissociate from DNA with a half-life of 15-36 min. Conclusion: DPCs on the translocating and nontranslocating strands constitute helicase and polymerase blocks, respectively. Significance: Reversible and irreversible protein roadblocks may have distinct effects on repliso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 61 publications
1
56
0
Order By: Relevance
“…DPCs, if left unrepaired, inhibit transcription as well as DNA unwinding during replication and may therefore result in genome instability or even cell death (Barker et al, 2005;Fu et al, 2011;Kohn et al, 2000;Nakano et al, 2013). Studies in yeast indicated that homologous recombination (HR) and nucleotide excision repair (NER) contribute to resistance toward FA exposure (de Graaf et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…DPCs, if left unrepaired, inhibit transcription as well as DNA unwinding during replication and may therefore result in genome instability or even cell death (Barker et al, 2005;Fu et al, 2011;Kohn et al, 2000;Nakano et al, 2013). Studies in yeast indicated that homologous recombination (HR) and nucleotide excision repair (NER) contribute to resistance toward FA exposure (de Graaf et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…azadC is incorporated into DNA and covalently traps the reaction intermediate of DNA cytosine methyltransferase, giving rise to DNA-protein cross-links (DPCs) [31]. DPCs block DNA replication and transcription [32,33] and hence constitute the major lethal lesions upon treatment with azadC. cisPt is a bifunctional DNA-damaging The treated cells were further incubated in fresh medium for 6 days, and colonies were scored to calculate the surviving fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DPCs form strong blocks for transcription by RNA polymerases when located on the transcribed strand 22 . Furthermore, DPCs (and DPC-mimicking biotin-streptavidin adducts) have been shown to inhibit the unwinding of the DNA duplex during replication in vitro 23,24 and, consequently, to interfere with replicationfork progression in vivo 25 . Interestingly, the effect of DPCs on the replicative helicase depends on whether they are located on the leading or the lagging strand 23,24 (FIG.…”
Section: Toxicity and Effects Of Dpcsmentioning
confidence: 99%
“…Hence, results obtained from studying specific DPCs might not always be generally extendable to others. Indeed, small DPCs (up to approximately 10 kDa) do not seem to inhibit replicative helicases 23 , and even the way and orientation in which a protein is crosslinked to DNA seems to be a crucial parameter for helicase stalling 23 . At any rate, DPCs interfere with DNA replication at various levels, and it is thus not surprising that DPC-inducing agents, such as formaldehyde, cause genomic instability, which manifests in micronuclei relieves torsional stress within DNA molecules by nicking one of the DNA strands.…”
Section: Toxicity and Effects Of Dpcsmentioning
confidence: 99%